Horrible Histories - The Measly Middle Ages : I Feel Like Black Death Warmed Up - Terry Deary (Scholastic London, United Kingdom, 1996)
This history book offers the chance to read about the wild women, mad monks, naughty knights and crackers kings and queens of the Middle Ages.
Keywords: Graphic Novels - History -- Graphic Novels - History